Minimum Wages Policy towards the employers in SME’s Industry. - Muhammad Zulfaris Mohd Salleh (2015)
Purpose of this study are to identify factors influencing employers on implementation of minimum wages policy, to find the impacts towards the implementation of minimum wages policy to the employers and to explores the readiness among employers regarding the implementation of minimum wages policy gazette by government.